The Relevance of the Precautionary Principle in Environmental Law Enforcement - Rhiti, Hyronimus; Chandavashti, Emilia Prasetya (CV. Rayyan Dwi Bharata, 2025)
Environmental degradation is one of the negative consequences of technological advancements and the increasingly massive development processes taking place. The environment is often viewed purely from an economic perspective, serving as a mere tool to satisfy human economic needs or, in some cases, to fulfill unchecked greed. The anthropocentric perspective, which places humans at the center of the human-nature relationship, is frequently blamed as the root cause of this issue. This article explores the precautionary principle as a fundamental legal doctrine that must be upheld in environmental law enforcement. The in dubio pro natura principle is closely related to this concept, asserting that when faced with uncertainty in resolving environmental disputes, judges must prioritize environmental sustainability. This study employs a normative legal research method with a conceptual and philosophical approach. The findings indicate that in dubio pro natura, as a principle intrinsically linked to the precautionary principle, must be firmly upheld by judges in handling environmental disputes. This principle is crucial in ensuring environmental sustainability for future generations thereby realizing the concept of intergenerational justice.